Avaliação da aprendizagem: métodos e instrumentos utilizados pelos docentes no 1º ciclo de alfabetização na EMEIF Gleba Pernambuco em Inhangapi-PA - ALBUQUERQUE, Sandro Raimundo Belém de (2020)
The work "Methods and Instruments used by teachers in the 1st cycle of literacy in E. M. E. F. Gleba Pernambuco in Inhangapi -PA" is a topic of great importance in the school context, especially in the first cycle of primary school literacy. Given this importance, the general objective of this research is to analyze the methods and instruments that the teachers of the Mun School. Ens. Inf. And Fund. Gleba Pernambuco use to evaluate the learning of the students of the 1st cycle of literacy. The specific objectives are: to know how the assessment of learning occurs in the 1st cycle of literacy and to identify which methods and instruments of evaluation are used by teachers of the first cycle of literacy. The work was consolidated through the application of a semistructured interview with the teachers of the mentioned school, dialoguing with theoretical bases such as: Jussara Hoffmann, Cipriano Luckesi, Celso Vasconcellos, Phillipe Perrenoud, among others. The results show that the evaluation methods and instruments used by teachers in the first cycle of literacy in EMEIF Gleba Pernambuco are observations, evaluative activities and tests, but they are not enough to accompany the students' full development. teachers need to use a variety of tools to obtain the diagnosis, taking into account the diversity in the learning of each learner. However, it is worth emphasizing that the evaluation is still an issue that is not very discussed within the scope of this school and that needs to be worked with continuing education for teachers.